Electric vehicle emulation based on inertial flywheel and a dc machine (2014)
This paper describes the analysis, modeling, and simulation of an electric vehicle (EV) focused on developing a test bench for reproducing EV dynamics. The EV test bench is composed of an induction motor (IM) drive, which is directly coupled to a dc machine and to an inertial flywheel through a transmission system with bands. The inertial flywheel and the DC machine reproduce the dynamic and forces acting on the EV. A methodology is proposed to design EV test bench to study the EV behavior close to the real test conditions. The EV forces and DC machine analysis can define the different conditions of the EV operation. The modeling and simulation are developed in MATLAB/Simulink, the test bench implemented is controlled by a DSP. Finally, simulation and experimental obtained results can validate the operation of the test bench emulator.